An architectural perspective on service adoption: A platform design and the case of pluggable cross-border trade compliance in e-commerce. Issue 4 (2nd October 2017) - Aulkemeier, Fabian; Iacob, Maria-Eugenia; van Hillegersberg, Jos
ABSTRACT: Current e-commerce architectures rely on a small number of monolithic application systems. The adoption of innovative IT functionality within these architectures is a tedious and complex task. The purpose of this article is to present a design for a novel platform architecture to improve the pluggability of e-commerce services. More precisely, the pluggability of services in current architectures is described, a platform architecture is introduced, and its effect on pluggability is evaluated by means of a prototype. The enablers for this architecture are the recent innovations of web programming interfaces, delegated resource access, and client-side web application frameworks. Those technologies are common in social media and their potential in enterprise computing is revealed in this work, based on the example of a trade compliance service for cross-border retail. The results of this study suggest that the architectural design has merits as it improves the pluggability of e-commerce services. Hence, e-commerce companies should consider a paradigm shift and move from using self-contained application components to a platform-based adoption of complementary services.